Drugs of choice from the medical letter (Medical Letter, Inc., 2001)
Contents: drugs for rheumatoid arthritis, drugs for asthma, cancer chemotheraphy, drugs for cardiac arrhythmias, drugs for depression and anxiety, drugs for epilepsy,...